Pengenalan dan Analisis Ucapan pada Sistem Kontrol Perangkat Listrik Menggunakan Arduino Uno - Dania Eridani; Ivan Sanusi; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This study aims to develop an electrical device control system using speech recognition and perform the analysis factors that affect the accuracy of speech recognition. The system used the Arduino Uno as the main control board of the system, an Elechouse's voice recognition module as speech processing device and several output devices such as relays, LEDs and an LCD. This research resulted in 92,7% accuracy of speech recognition at the ideal condition and 66,85% at the noise condition. This study shows that the frequency, amplitude, slow tempo and timbre of command speech greatly affect the success of speech recognition.